(untitled) (Research, Society and Development, 2021)
Many mistakes are made due to the difficulty in using tools in the search for identification and selection of talents in the sport. This study analyzed the relationship between the birth quartile and the maturation stage of young athletes. A total of 238 individuals were selected, having practiced sports for at least one year, of both sexes (12.4 ± 2.16 years). The birth dates were distributed according to the corresponding birth quartiles. The evaluation of maturation was performed by subtracting bone age from chronological age, bone age was measured by a highly reliable mathematical model that uses anthropometric variables. The birth quartiles were not associated with the biological maturation stage (male: r = 0.03, p = 0.6; female: r = 0.04, p = 0.6). The birth quartiles were not significant for predicting the biological maturation stage (male: β = 0.15, p = 0.1; female: β = 0.8, p = 0.1). In both sexes, when considering the birth quartiles, the maturation stages did not show significant differences (p = 0.2) and the subjects born in the same year and quartile presented different levels of biological maturation (η²p <0.22). Such results suggest that there is no correlation between birth quartiles and maturation stages.